2008
DOI: 10.1063/1.2819091
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of colloidal hard perfect tetragonal parallelepipeds

Abstract: The phase behavior of suspensions of colloidal hard tetragonal parallelepipeds ("TPs") (also known as rectangular nanorods or nanobars) was studied by using Monte Carlo simulations to gain a detailed understanding of the effect of flat-faceted particles on inducing regular local packing and long range structural order. A TP particle has orthogonal sides with lengths a, b, and c, such that a=b and its aspect ratio is r=c/a. The phase diagram for such perfect TPs was mapped out for particle aspect ratios ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 27 publications
4
94
1
Order By: Relevance
“…In contrast to earlier conjectures [11][12][13] , we now find clear evidence of layering in the cubatic phase (also observed in [32]) which becomes visible in our redefined particle distribution functions (see details in SI). While the finite size of our system prevents us from ascertaining the range of such a positional order, the appreciable D values observed at these densities indicates that the system has liquid-like behaviour and there is sufficient translational disorder for layers to rearrange dynamically.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to earlier conjectures [11][12][13] , we now find clear evidence of layering in the cubatic phase (also observed in [32]) which becomes visible in our redefined particle distribution functions (see details in SI). While the finite size of our system prevents us from ascertaining the range of such a positional order, the appreciable D values observed at these densities indicates that the system has liquid-like behaviour and there is sufficient translational disorder for layers to rearrange dynamically.…”
contrasting
confidence: 99%
“…These ordered assemblies have distinctive electronic, optical, and dynamical properties 4,5 and are highly desirable for fabrication of advanced electronic, photonic, and rheological devices 6,7 . Although numerous theoretical [8][9][10][11][12][13] and experimental 14,15 studies on mesophase behaviour of particles with anisotropic shapes have been reported, a roadmap marking out the most probable mesophases that could be formed by constituent particles with particular geometrical features is still incomplete. Exploring such relations will translate into a deeper understanding of the phase behaviour of colloidal systems with different particle shapes; e.g., Jiao et al 16 reported that unlike ellipsoids, convex superballs can be optimally packed in dense Bravais lattices because they are less symmetric but more isotropic than the former.…”
mentioning
confidence: 99%
“…A recent simulation work [33] analysed the full phase diagram of board-like particles with square cross section, σ 1 = σ 2 and 0.125 < σ 3 /σ 1 < 0.5. The first condition is not compatible with the formation of the the biaxial-nematic phase.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters F (2) 20 and F (2) 22 are zero in the uniaxial phase and nonzero in the biaxial phase. In the limit of the perfect uniaxial order ( F were computed in the Monte Carlo simulations of hard tetragonal parallelepipeds [58] in order to identify the cubatic (parquet) phase.…”
Section: Orientational Distribution Functionmentioning
confidence: 99%